2020
DOI: 10.3390/antiox9111148
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Activity and Acteoside Analysis of Abeliophyllum distichum

Abstract: This study determined acteoside and its content in Abeliophyllum distichum via HPLC/UV and LC/ESI-MS to obtain insights into the potential use of this plant as an antioxidant agent. Moreover, 1,1-diphenyl-2-picrylhydrazyl (DPPH), hydroxyl (•OH), and O2− radical scavenging activity assays were performed to assess in vitro antioxidative activity. The DPPH, •OH, and O2− radical scavenging activities of A. distichum leaf EtOH extracts at a 250 μg/mL concentration were 88.32%, 94.48%, and 14.36%, respectively, wher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 36 publications
(44 reference statements)
0
17
0
Order By: Relevance
“…In addition, AB displayed a stronger ability to decrease DPPH free radicals (RC 50 = 294.5 ± 16.4 µg/mL, Figure 1 C), ABTS cation radicals (RC 50 = 36.0 ± 0.63 µg/mL, Figure 1 D), and hydroxyl radical scavenging activity (86 ± 0.97%) than other organ extracts, suggesting that A. distichum branches possess a stronger antioxidant activity than that of the other analyzed organs. Recently, it has been shown that antioxidant activity of A. distichum leaf EtOH extracts is slightly higher than A. distichum stem EtOH extracts [ 15 ]. The variation of antioxidant activity might be mediated by phytochemical compositions and concentrations, which are influenced by season, climatic conditions, stages of maturity, and extraction conditions.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition, AB displayed a stronger ability to decrease DPPH free radicals (RC 50 = 294.5 ± 16.4 µg/mL, Figure 1 C), ABTS cation radicals (RC 50 = 36.0 ± 0.63 µg/mL, Figure 1 D), and hydroxyl radical scavenging activity (86 ± 0.97%) than other organ extracts, suggesting that A. distichum branches possess a stronger antioxidant activity than that of the other analyzed organs. Recently, it has been shown that antioxidant activity of A. distichum leaf EtOH extracts is slightly higher than A. distichum stem EtOH extracts [ 15 ]. The variation of antioxidant activity might be mediated by phytochemical compositions and concentrations, which are influenced by season, climatic conditions, stages of maturity, and extraction conditions.…”
Section: Resultsmentioning
confidence: 99%
“…The absorbance was measured at 532 nm, after incubation for 30 min at 90 °C. Hydroxyl radical scavenging activity was calculated as described by Lee et al [ 15 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The major phenolic compounds were identified in each extract ( Figure 3 ) based on their retention index and their PDA spectrum with comparison to a library. Results showed that all extracts were characterized by high quantities of isomers of acteoside, a phenolic molecule well known for its wide range of biological properties including anti-inflammatory, antioxidant and hepatoprotective activities [ 51 , 52 , 53 , 54 , 55 ].…”
Section: Resultsmentioning
confidence: 99%